The use of indigenous plants as food by a rural community in the Eastern Cape : an educational exploration - Shava, Soul (Rhodes University, Faculty of Education, Department of Education, 2000)
Looking at the use of plants as food reflects how humankind has fashioned nature. There has been a significant change in production patterns from hunter-gathering through subsistence agriculture to technologically advanced commercial agriculture with a subsequent reduction in the diversity of plants used as food. A parallel trend in consumption patterns has occurred, from home-based food processing for subsistence through small- scale production to large-scale industrial processing and the commodification of food. The overall result of such trends is a narrowing of the food resource base and an increasing reliance on processed foods at the expense of traditional diets, accompanied by increasing diet-related health risks. This research is an ethnographic case study on the use of indigenous food plants by the community of Tuku A village in the Eastern Cape using interviews and observations as the main data collecting strategies. A nutritional analysis of some wild food plants was also carried out. An inventory of more than 70 food plant species was compiled, with the knowledge of such plants found among both the elderly and the youth. The incorporation of this knowledge into education systems is recommended. Of the wild food plants documented, some were non-indigenous indicating the dynamic nature of indigenous knowledge. Some wild spinach were left to grow amongst cultivated food plants, hinting at some form of 'domestication' in process. This observation together with the observation that wild fruit trees were selectively conserved highlights the possibility of the continued use of wild food contributing to conservation of botanical diversity. Community use of indigenous food was found to be diminishing. Stigmatisation of indigenous food plants, urbanisation, formal education, changes in lifestyle, and media were some of the factors possibly influencing this dietary shift. The community made links between diet and health, which correspond to modern scientific knowledge, with modern diet being lamented for ill health. The nutritional analysis revealed that wild food plants do contain essential dietary nutrients, an area recommended for further research.
Keywords: Plants, Edible -- South Africa -- Eastern Cape; Wild plants, Edible -- South Africa -- Eastern Cape; Human-plant relationships -- South Africa -- Eastern Cape; Endemic plants -- South Africa